Towards a creative psychological practice: Preparing for the attention to diversity - Cupertino, Christina (2008)
An atypical psychological intervention, the Creativity Workshops, understood as the possibility of transformation of people, environments and/or relationships, which took place in a social Project for youths in the outskirts of Sao Paulo, is presented. Resources common to artistic expression, located in the interface between Art, Psychology, and Education were used, as well as activities of Organic Music (or corporal percussion), offered for the youngsters of the pop-rock band classes of the institution. It is discussed how the abandonment of the expectations and the opening to significant exchanges allowed the establishment, finally, in an unexpected place, of the space in where psychological care could take place, flowing and transitory as the movement of life, creating new ways of professional insertion.